Two lathyrane diterpenoid stereoisomers containing an unusual trans-gem-dimethylcyclopropane from the seeds of Euphorbia lathyris. Issue 5 (14th January 2021) - Li, Linwei; Huang, Jianan; Lyu, Hui; Guan, Fuqin; Li, Pirui; Tian, Mei; Xu, Shu; Zhao, Xingzeng; Liu, Fei; Paetz, Christian; Feng, Xu; Chen, Yu
Abstract : Two novel lathyrane-type diterpenoids, which possess a trans-gem -dimethylcyclopropane were obtained from seeds of Euphorbia lathyris . The Euphorbia factor L2b exhibited an inhibitory effect against U937 cell line with an IC50 value of 0.87 μM. Abstract : Two novel lathyrane-type diterpenoids, the Euphorbia factors L2a (1 ) and L2b (2 ), and their stereoisomer Euphorbia factor L2 (3 ) were obtained from seeds of Euphorbia lathyris . Both Euphorbia factors L2a and L2b possess an unprecedented trans-gem -dimethylcyclopropane as structural feature. Also, the Euphorbia factor L2a is the first example of a lathyrane diterpenoid with an endocyclic 12( Z )-double bond. The structures of the molecules and their absolute configurations were elucidated by comprehensive spectroscopic analyses, Cu-Kα radiation X-ray diffraction, and comparison with calculated electronic circular dichroism (ECD) data. The Euphorbia factor L2b exhibited an inhibitory effect against U937 cell line with an IC50 value of 0.87 μM.